1944
DOI: 10.1104/pp.19.4.679
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Photosynthesis and Respiration in Red and Loblolly Pines

Abstract: The growth of red pine (Pinus resinosa Ait.) planted in the Duke Forest has been very slow compared with the expected growth of this species within its niatural range. Seedlings which were three years old when planted attained an average height of only 2.36 feet after eight growing seasons (8).The average height of fifteen-year-old red pine saplings on medium sites in Connecticut was about 17.5 feet (7).There is no evidence of damage to the young trees by fungi nor by insects. The soil of the plot on which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

1944
1944
1969
1969

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…The natural fluctuations in temperature might have considerable effect on the rate of apparent photosynthesis through changes in the rate of respiration. DECKER (3) found the apparent photosynthesis of loblolly pine to be nearly twice as high at 30°as at 40°C. and the rate of respiration to be over 50 per cent.…”
Section: (With Two Figures)mentioning
confidence: 99%
“…The natural fluctuations in temperature might have considerable effect on the rate of apparent photosynthesis through changes in the rate of respiration. DECKER (3) found the apparent photosynthesis of loblolly pine to be nearly twice as high at 30°as at 40°C. and the rate of respiration to be over 50 per cent.…”
Section: (With Two Figures)mentioning
confidence: 99%
“…DECKER (8) found that temperature had no effect on photosynthesis in some conifers. VERDUIN and LooMIs (24), working with maize leaves in the field, observed no correlation between moderately high temperatures and photosynthesis.…”
Section: The Temperature Coefficient Of Photosynthesis Under Field Comentioning
confidence: 99%
“…In the field, however, Q,o values near 1.0 have been demonstrated for photosynthesis within the range of 20 to 400 C (1, 6,8,23,24). Reduction in leaf hydration is assumed to check photosynth1esis.…”
mentioning
confidence: 99%
“…KRAMER and DECKER (12) state that "in preliminary experiments at 30°C the rate of photosynthesis in oaks began to decrease rapidly after five or six hours at a high light intensity." DECKER (5) found that in preliminary measurements of the rate of photosynthesis in red alnd loblolly pines at temperatures of 20°, 300, and 400 C the rate remained unchanged for at least six hours at a light intensity of 4500 foot candles.…”
Section: Introductionmentioning
confidence: 99%